Translation of microwave methodology to continuous flow for the efficient synthesis of diaryl ethers via a base-mediated SNAr reaction - Wiles, Charlotte; Watts, Paul (Beilstein Journal of Organic Chemistry, 2011)
Whilst microwave heating has been widely demonstrated as a synthetically useful tool for rapid reaction screening, a microwave-absorbing solvent is often required in order to achieve efficient reactant heating. In comparison, microreactors can be readily heated and pressurised in order to “super-heat” the reaction mixture, meaning that microwave-transparent solvents can also be employed. To demonstrate the advantages associated with microreaction technology a series of SNAr reactions were performed under continuous flow by following previously developed microwave protocols as a starting point for the investigation. By this approach, an automated microreaction platform (Labtrix® S1) was employed for the continuous flow synthesis of diaryl ethers at 195 °C and 25 bar, affording a reduction in reaction time from tens of minutes to 60 s when compared with a stopped-flow microwave reactor.
Keywords: automated synthesis; continuous flow; microreactor; microwave; nucleophilic substitution; organic bases